Ukraine : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes the extent of corruption in Ukraine compared with other countries. The level of corruption in Ukraine is exceptionally high. This could severely undermine economic growth prospects by hindering private investment. Reducing corruption is therefore essential to speed economic convergence with the rest of Europe. Regional comparisons help identify best practices in reducing corruption. The Ukrainian authorities have recently adopted key measures that follow some of these best practices. The country is, however, facing several challenges, including the concentration of political and economic power in a small group of people, which may hamper effective anticorruption efforts.